Shareholder preferences concerning corporate ethical performance - Epstein, Marc J. (Journal of business ethics, 1994)
This study surveyed investors to determine the extent to which they preferred ethical behavior to profits and their interest in having information about corporate ethical behavior reported in the corporate annual report. First, investors were asked to determine what penalties should be assessed against employees who engage in profitable, but unethical, behavior. Second, investors were asked about their interest in using the annual report to disclose the ethical performance of the corporation and company officials. Finally, investors were asked if they felt that ethics reports should be audited., The survey results indicate that many shareholders (42%) do not expect a high level of ethical behavior from corporate employees or officers. There is a significant amount of interest in disclosure of ethical issues (72%) and unwillingness to trust management to provide unbiased reports of ethical behavior. If such reports are included with the financial statements, 32 percent of the investors surveyed would prefer to have them audited to provide independent verification.